PENGARUH PENGALAMAN, INDEPENDENSI, DAN KOMPETENSI PEMERIKSA TERHADAP KUALITAS PEMERIKSAAN: (Studi Kasus pada BPK RI Perwakilan Provinsi NTT) - SONLY NENDIARIE; SULAIMAN; AKBAR YUSUF (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2015)
This study aims to examine the relationship variables experience, independence and competence ofauditors to audit quality, either partially or simultaneously, and the variable competence ofauditors as a moderation in the relationship between the auditor's independence with audit qualityusing a sample population of auditor BPK RI Perwakilan Provinsi NTT totaling 61 person. Theanalysis technique used is multiple linear regression and Moderated Regression Analysis (MRA).The results showed that either partially or simultaneously, variable experience, independence, andcompetence examiner positive effect on audit quality. While the different results are found in theinteraction with the independence and competence of auditors who audit quality does not have arelationship. To develop this research, it is recommended that future researchers: a) using theresearch instrument in accordance with the characteristics of the institution / organizationexaminer, b) can extend the area of research and increase the number of samples in other workunits on the BPK Republik Indonesia so the results can be generalized, c) may consider to addother variables that can affect the quality of the examination.